1985
DOI: 10.1002/esp.3290100411
|View full text |Cite
|
Sign up to set email alerts
|

The effect of road construction on sediment deposition in Loch Earn, Scotland

Abstract: In 1982 an unmetalled road was constructed in a Scottish Highland glen, Glen Ogle, crossing several left bank tributaries of the Ogle Burn, one of the main influents to Loch Earn. As a result, at least 1824 tonnes of sediment were deposited over an area of 4.6 ha of loch bed in less than 2 months. This was over 20 times as much material by weight than had passed a temporary gauging station, near the confluence with the loch, during an earlier 12 month monitoring period. The mean thickness of the resultant depo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Increased suspended sediment loads during highway construction have been well documented (Duck 1985, Hainley 1980, Helm 1978, Helsel 1985, Peterson and Nyquist 1972. These increases have the potential of adversely affecting stream channel characteristics a s well a s biological communities (Helsel 1985).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Increased suspended sediment loads during highway construction have been well documented (Duck 1985, Hainley 1980, Helm 1978, Helsel 1985, Peterson and Nyquist 1972. These increases have the potential of adversely affecting stream channel characteristics a s well a s biological communities (Helsel 1985).…”
Section: Discussionmentioning
confidence: 97%
“…Studies have shown that highway construction increases suspended sediment levels up to 10 krn downstream (Downs and Appel 1986, Duck 1985, Hainly 1980, Helm 1978, Peterson and Nyquist 1972. Return to pre-construction suspended sediment levels is dependent on topography and climate of the watershed and erosion control methods (Helm 1978).…”
Section: Introductionmentioning
confidence: 98%
“…While there are overseas studies of sediment yield from roadways (Younkin, 1973;Hafley, 1975;Burton et ai, 1976;Duck, 1985) there are no detailed studies in Australia. Several studies of forest areas in Eastern Australia clearly demonstrate the significant contribution that roads make to sediment yield in disturbed (logged and burnt) catchments (Burgess et al, 1981;Langford et al, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Road construction along stream corridors alters the structure, function, and stability of stream channels Ball 1965, Albanese andMatlack 1998). Road crossings such as bridges and culverts can influence stream hydraulics and sediment transport (Duck 1985, Johnson 2002. Bridges can either be single span, with no pillars in the stream, or multiple span, with one or more pillars in the stream.…”
Section: Monitored Benthic Macroinvertebrates At Four Sites On Turtlementioning
confidence: 99%
“…Many studies have assessed effects of sedimentation or siltation , but a review by found inconsistent patterns of environmental impacts among studies. Some important impacts to stream environments from highway construction include an increase in inorganic sediments due to erosion of exposed, unvegetated channel banks (Urban and Rhoades 2003), an increase in erosion of the disturbed land surface due to recontouring and leveling (Wohl 2000, Wohl 2006, and alteration of the natural stream channel by channel realignment, placement of culverts and construction of bridges (Duck 1985, Johnson 2002. The following literature review includes sections on the impacts of sedimentation, the effects of sedimentation on benthic macroinvertebrates, assessing sedimentation, and effects of construction on stream channels.…”
mentioning
confidence: 99%